Assessing the internal consistency and temporal stability of advance directives generated by an interactive, online computer program. Issue 1 (5th March 2015) - Schubart, Jane R; Camacho, Fabian; Green, Michael J; Rush, Kimberly A; Levi, Benjamin H
Abstract : Objective: Evaluate the internal consistency and temporal stability of advance directives (ADs) generated by an interactive, online computer program. Methods: 33 participants completed the program at three visits, 2 weeks apart. Agreement rates were calculated for the General Wishes component of the AD. The test–retest method was used to examine the temporal stability of the Specific Wish for Treatment component which contains five clinical scenarios. Results: General Wishes remained stable with 94% selecting the identical response at each visit. For the Specific Wish for Treatment scale, significant variations in test–retest correlations existed (ie, ρ=0.32–0.78, between time points 1 and 2); however within scenario, correlations did not significantly vary between time points. Temporal stability was lower in the Specific Wish for Treatment scale compared with General Wishe s (average ρ=0.59, between time points 1 and 2; and ρ=0.75, between time points 2 and 3). Conclusions: ADs generated by an online decision aid demonstrate good temporal stability, with highest stability for General Wishes and moderate stability for Specific Wish for Treatment regarding medical treatments in specific clinical scenarios. Internal consistency for wish for treatment across all time points and scenarios was high (Cronbach α>0.90).